Analisis sistem pengendalian manajemen UMKM Bento Kopi sebagai upaya meningkatkan kinerja karyawan - Yuli Fatmilia; Elza Levina Syahda; Ratna Purnama (Department of Accounting Universitas PGRI Yogyakarta, 2023)
A management control system is a system that is used to control activities within a company in order to comply with a defined goal. In improving quality and quantity of products, it is very important to pay attention and evaluate employee performance so a good management control system is needed. The object of this research is Bento Kopi Yogyakarta. The aim of this study are (1) analyze whether the management control system at Bento Kopi is running in a structured and good manner (2) find out how the process of the management control system works in an effort to improve employee performance. The method used in this study is a qualitative method with a descriptive analysis method. The results of the research show that the process of management control in improving employee performance is optimal and maximum. As well as the implementation of the Standard Operating Procedure (SOP) and ethical guidelines at Bento Kopi have been fully implemented so that it can improve employee performance from the perspective of consumers andcompanies. Keywords : Management Control System, Employee Performance, Standard Operating Procedure, Qualitative method